2021
DOI: 10.1016/j.acvd.2021.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on the incidence of cardiac arrhythmias in implantable cardioverter defibrillator recipients followed by remote monitoring

Abstract: Background: The coronavirus disease 2019 (COVID-19) has been a fast-growing worldwide pandemic. Aims: We aimed to investigate the incidence of cardiac arrhythmias among a large French cohort of implantable cardioverter defibrillator recipients over the first 5 months of 2020. Methods: 5954 implantable cardioverter defibrillator recipients were followed by remote monitoring during the COVID-19 period (from 01 January to 31 May 2020). Data were obtained from automated remote follow-up of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…We acknowledge that the study enrolled a very selected group of patients to carefully investigate a specific feature (ie, PA) in the three considered periods. Thus, results requiring larger samples to be demonstrated could not be found, as in the case of ventricular arrhythmias whose highest incidence was a mean of 0.09 (SD 1.2) episodes per patient per week in a previous study on the COVID-19 pandemic and remote monitoring [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that the study enrolled a very selected group of patients to carefully investigate a specific feature (ie, PA) in the three considered periods. Thus, results requiring larger samples to be demonstrated could not be found, as in the case of ventricular arrhythmias whose highest incidence was a mean of 0.09 (SD 1.2) episodes per patient per week in a previous study on the COVID-19 pandemic and remote monitoring [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…We did not find any increased incidence of ventricular arrhythmias during the COVID-19 pandemic in non-infected patients, consistent with previous studies on the topic. 4–6 , 17 However, we found that, during the COVID-19 pandemic, the incidence of AF was higher than during the pre-COVID-19 period. Among the previous four studies on this topic, only one study from France mentioned atrial arrhythmia (the others only investigated ventricular arrhythmia burden); the authors demonstrated no changes regarding the evolution of atrial fibrillation/tachycardia episodes during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 61%
“…Among the previous four studies on this topic, only one study from France mentioned atrial arrhythmia (the others only investigated ventricular arrhythmia burden); the authors demonstrated no changes regarding the evolution of atrial fibrillation/tachycardia episodes during the COVID-19 pandemic. 17 The most likely explanation for the observed discrepancy was that the authors only studied the evolution of the incidence of atrial fibrillation/tachycardia episodes during the epidemic period and did not compare it with the pre-COVID-19 period. Additionally, we found a sudden increase in daily NSVT duration after the first COVID-19 case in Wenzhou, China, was declared and a significant drop after the final case recovered on 16 March 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Since the association between asymptomatic viral infection and arrhythmia risk has not been clearly established, as suggested by few published studies, 15,22 and although none of the studied patients was hospitalized for COVID‐19 infection or respiratory illness, we are not able to exclude that asymptomatic COVID infections may have influenced our results.…”
Section: Limitations Of the Studymentioning
confidence: 89%
“…Another important study that needs to be considered is published by Galand et al 22 on a very large cohort of patients with ICD and CRTD in France. In this study, an increase in VA was observed after the first Covid case and especially during the 2 weeks before lockdown at the time of major government measures; then, after the lockdown order, the incidence of VA dropped significantly.…”
Section: Discussionmentioning
confidence: 99%